(3JGQjN edhc GdahfL HGdShOGf hCbGdjeg Edi Mce eMeO HGTG SYjOs
(3ChdgG (B:s
(3GdMeO ddg eHOF GdNdb heYjOg s
(3eUhQI Yf fSNI eMahXI HGdecJHI GdCgdjI HHGQjSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B895 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B73 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B2547) s
Keywords: (3GdJGQjNs